Soil classification in Belarus: history and current problems - Tsyrybka, Viktar; Ustsinava, Hanna (Bulletin of Geography. Physical Geography Series, 2018)
The article contains brief history of development of the soil classification framework of Republic of Belarus. Itcomprisesthedescriptionofthemostwidely-used(acknowledged) genetic classification of soil, characteristics of basic taxonomic units (type, subtype, sort, kind, variation), characteristics of 13 main types of Belarusian soils.A small-scale map of the soil cover of Belarus is presented, as well as the morphological and genetic characteristics of typical and unique soil varieties. The article illustrates modern tendencies of creating new frameworks of soil classification tailored to the nature of anthropogenic influence, as well as the unique 8-level digital classification framework enabling the creation of soil’s digital genetic code.